Are women neglected in the EU agriculture? Evidence from Lithuanian young farmers. (February 2021) - Balezentis, Tomas; Morkunas, Mangirdas; Volkov, Artiom; Ribasauskiene, Erika; Streimikiene, Dalia
Highlights: Gender-wise differences in the perceptions of young farmers. The measures of the Common Agricultural Policy. Development of farms and the use of advisory services. The results show gender equality in Lithuanian agriculture. Abstract: The agriculture in Eastern Europe has seen a number of economic and social transitions. This research examines the gender inequality in agriculture by taking the case of an Eastern European country – Lithuania – as an example. The questionnaire survey was employed in order to check the existence of gender inequality. The study focuses on the young farmers as they are more likely to implement innovations and shape the future agricultural activities. The demand for advisory services and participation in the Common Agricultural Policy measures were used to compare the activities and perceptions of men and women young farmers. We found that there are no significant differences in participation of support measures and demand for advisory services across the genders. This suggests Lithuanian agricultural sector is equally beneficial for men and women young farmers. Given the differences in the educational background, a positive effect is anticipated if women were more empowered in Lithuanian agriculture. Women's participation in agriculture could increase environmental awareness, propensity to innovate and economic resilience.